2000
DOI: 10.1118/1.1288669
|View full text |Cite
|
Sign up to set email alerts
|

X-ray videodensitometric methods for blood flow and velocity measurement: A critical review of literature

Abstract: Blood flow rate and velocity are important parameters for the study of vascular systems, and for the diagnosis, monitoring and evaluation of treatment of cerebro- and cardiovascular disease. For rapid imaging of cerebral and cardiac blood vessels, digital x-ray subtraction angiography has numerous advantages over other modalities. Roentgen-videodensitometric techniques measure blood flow and velocity from changes of contrast material density in x-ray angiograms. Many roentgen-videodensitometric flow measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
111
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 138 publications
1
111
0
1
Order By: Relevance
“…DSA has been used for flow quantification before, and it has been used by others for velocity measurement, [16][17][18] and aneurysmal flow evaluation. [9][10][11] These studies demonstrate that the change of signal does have a potential to assist us in understanding the hemodynamics in arteries and aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…DSA has been used for flow quantification before, and it has been used by others for velocity measurement, [16][17][18] and aneurysmal flow evaluation. [9][10][11] These studies demonstrate that the change of signal does have a potential to assist us in understanding the hemodynamics in arteries and aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that this parameter leads to better results 12 compared with other criteria, such as the time-to-maximum-slope parameter. An overview of typically used alternative bolus arrival time criteria is, for example, given by Shpilfoygel et al 13 The TTP parameter is especially important for 4D MRA imaging techniques because it reflects the temporal distribution of the contrast agent and can, therefore, be used as an indirect estimate of the blood flow velocity. Due to the discrete IDC representation, recirculation effects, and noise artifacts, which affect the shape of the curves, the direct estimation of the TTP parameter is often imprecise.…”
Section: Time-to-peak Criterion and Parametric Modelsmentioning
confidence: 99%
“…6 Concentration Time Curves (CTC) track the bolus propagation by observing the change of pixel intensity ( Fig. 2(a)) while Concentration Distance Curves (CDC) track the front propagation of the bolus.…”
Section: Measuring Projective Blood Flowmentioning
confidence: 99%
“…An extensive review of recovering blood flow velocity from projective images was done by Shpilfoygel et al 6 A method similar to our approach was published by Schmitt et al 7 The work aims at determining the contrast agent (CA) propagation in vessel trees. The method also relies on a re-projection of 2D-DSA images to 3D-RA volumes.…”
Section: Introductionmentioning
confidence: 99%